Achieving phosphorus recovery at pilot-scale anaerobic anoxic/nitrifying-induced crystallization (A2N-IC) process: Performance, assessment, and challenges. (February 2023) - Li, Xiang; Shen, Shuting; Fu, Zhiqiang; Dong, Yiran; Dai, Hongliang; Lu, Xiwu
Abstract: A pilot-scale anaerobic-anoxic/nitrifying/induced crystallization (A2 N-IC) process was established for phosphorus (P) recovery and nutrient removal from municipal wastewater with a treatment capacity of 80 m 3 d -1 . Results show that the A2 N-IC process can operate stably on a pilot scale; the recovery efficiency of influent P reached 62.2%, and the total P removal efficiency of the IC section was 65.4%. The IC section had little effect on the removal of chemical oxygen demand (COD) and nitrogen (N), and the P removal efficiency was improved. Soluble non-reactive P (sNRP) was the key factor affecting P recovery efficiency. Although P recovery increases the construction and maintenance costs, the process can be profitable if a market for P recovery products is established. To improve the P recovery efficiency, attention should be paid to the effects of sNRP and dissolved organic matter (DOM) on P recovery, and P-rich sludge should be considered. Graphical abstract: Image 1 Highlights: An 80 t/d anaerobic-anoxic/nitrifying/induced crystallization phosphorus recovery process was established. 62.2% of influent total phosphorus was recovered. The removal and effect of non-reactive phosphorus were analyzed. The economy of A2N-IC process is evaluated.